EPR and FTIR Spectroscopies Study of Human Blood after Irradiation. Issue 5 (11th July 2012) - Polakovs Polakovs, M. M.; Mironova-Ulmane Mironova-Ulmane, N. N.; Pavlenko Pavlenko, A. A.; Reinholds Reinholds, E. E.; Gavare Gavare, M. M.; Grube Grube, M. M.
Abstract : In the present work we report results of investigations of human blood before and after radioisotopeTc 99m diagnosis by electron paramagnetic resonance (EPR) and Fourier transform infrared (FTIR) spectroscopies. It is shown that EPR can detect the concentration of methaemoglobin and transferrin ions more accurately than any other technique. FTIR spectra indicated that radiation caused conformational and concentration changes of proteins. Hierarchical cluster analysis (HCA) was created as time-saving tool for discrimination of initial and irradiated in vivo human blood samples.